How Can Enterprise Digital Transformation Facilitate Internationalization? - Gang Li; Chunlian Zhang; Ling Hu (SAGE Open)
Enterprises face cross-border legal, cultural, technical differences, market volatility, and cybersecurity threats during internationalization, needing resource investment for organizational agility and supply chain security to maintain global competitiveness. China, a major global outbound investor, had US $177.29 billion in outward FDI in 2023 (11.4% of global total), ranking top three for 12 years, and its outward FDI stock was US $2.96 trillion by end-2023, keeping a top-three global spot for 7 years. This study draws on a dataset comprising 40,251 annual observations of outward investment activities by A-share listed companies in China from 2010 to 2019. In this study, we leverage binary selection variables and employ the following Probit regression model as our benchmark specification. In this study, we adopt the following Probit regression model as our benchmark and conduct all subsequent regression analyses using Stata. This study highlights the pivotal role of digital transformation in advancing enterprise internationalization. Elevating digital proficiency and operational performance, while trimming transaction costs, allows businesses to more effectively broaden their international presence. The substantial influence of digital transformation on global capital flows and corporate expansion offers a theoretical basis for policymakers. This allows them to formulate strategies that foster digital innovation, upgrade infrastructure, and lower financing costs, thus promoting both digitalization and international growth. Financing constraints, equity concentration, access to regional bank loans, and the degree of marketization influence how digital transformation affects outward foreign direct investment (OFDI).